The effect of support locations on the steady-state response of viscoelastically point-supported rectangular orthotropic plates - Kocatürk, T; Sezer, S; Demir, C (SPRINGER, 2005)
The vibration of orthotropic rectangular plates having viscoelastic point supports symmetrically located on its diagonals is analyzed. The plate is under the effect of a sinusoidally varying force at its center. The Lagrange equations are used in the solution process. To apply the Lagrange equations, the trial function denoting the deflection of the plate is expressed in polynomial form. By using the Lagrange equations the problem is reduced to the solution of a system of algebraic equations. The influence of the mechanical properties, the damping of the supports and the locations of point supports on the steady-state response of the viscoelastically point-supported rectangular plates is investigated numerically for the concentrated load at center for various values of the mechanical properties characterizing the anisotropy of the plate material and for various values of damping and location of the supports for a certain stiffness value of the supports. The results are given for the considered frequency range of the external force. Convergence studies are made. The validity of the obtained results is demonstrated by comparing them with other solutions based on the Kirchhoff-Love plate theory.
Keywords: viscoelastic point supports; elastic point supports; orthotropic plates; viscoelastically point-supported; plates; steady-state response of viscoelastically point-supported plates; VIBRATIONS; Mechanics